Exploring the multi-level perspective in municipal solid waste management transition. (November 2022) - Iyamu, H.O.; Anda, M.; Ho, G.
Abstract: The successful transition of municipal solid waste management (MSWM) in low-income economies towards a more sustainable practice is dependent on socio-political drivers, enablers/interventions, and service delivery practices. However, Environmental and sustainability sub-components influence this transition initiatives regarding sustainable MSWM. Informed by the theory of Multi-Level Perspective (MLP), we developed a nuanced Dimensional Evaluation of Waste Transition (DEWasT) model for MSWM to clarify societal factors and triggers for sustainability. This model elucidates the transition of MSWM, characterised by the three-level MLP, namely, landscape pressures, regimes, and niche innovations. The interaction of these transition levels within this model allows policymakers, institutions, and stakeholders to understand the current structure and dynamics. It will enable practical guidelines for MSWM sustainability practices, influencing a paradigm change towards MSWM innovations in low-income economies and closing the gaps identified by previous practitioners. Highlights: The development of a nuanced municipal solid waste management (MSWM) transition model. The Dimensional Evaluation of Waste Transition (DEWasT) model improves sustainable practices. The Multi-Level Perspective's (MLP's) innovative approach is used for bridging strategies and furthering sustainability. DEWasT model informs MSWM transition, clarifies societal factors, and triggers sustainability.